A Pooled Analysis of Biochemical Failure in Intermediate-risk Prostate Cancer Following Definitive Stereotactic Body Radiotherapy (SBRT) or High-Dose-Rate Brachytherapy (HDR-B) Monotherapy. (May 2018) - Hegde, John V.; Collins, Sean P.; Fuller, Donald B.; King, Christopher R.; Demanes, D. Jeffrey; Wang, Pin-Chieh; Kupelian, Patrick A.; Steinberg, Michael L.; Kamrava, Mitchell
Abstract : Objectives: To investigate biochemical relapse-free survival (BRFS) in men with National Comprehensive Cancer Network-defined intermediate-risk prostate cancer (PC) treated with either stereotactic body radiotherapy (SBRT) or high-dose-rate brachytherapy (HDR-B) monotherapy. Materials and Methods: A retrospective, multi-institutional analysis of 437 patients with intermediate-risk PC treated with SBRT (N=300) or HDR-B (N=137) was performed. Men who underwent SBRT were treated to 35 to 40 Gy in 4 to 5 fractions. A total of 95.6% who underwent HDR-B were treated to 42 Gy in 6 fractions. Baseline patient characteristics were compared using a T test for continuous variables and the Mantel-Haenszel χ 2 metric or Fisher exact test for categorical variables. Kaplan-Meier curves were generated to estimate 5-year actuarial BRFS. Multivariate analysis using a Cox proportional-hazards model was used to evaluate factors associated with biochemical failure. Results: The mean age at diagnosis was 68.4 (SD±7.8) years. T-category was T1 in 63.6% and T2 in 36.4%. Mean initial prostate-specific antigen was 7.4 (SD±3.4) ng/mL. Biopsy Gleason score was ⩽3+4 in 82.8% and 4+3 in 17.2%. At a median of 4.1 years of follow-up, the BRFS rate (Phoenix definition) was 96.3%, with no difference when stratifying by treatment modality or biologically equivalent dose (BED1.5 ). On multivariate analysis, age (hazard ratio 1.08, P =0.04) and biopsy Gleason score (hazard ratio 2.48, P =0.03) were significant predictors of BRFS. Conclusions: With a median follow-up period of 4 years, SBRT and HDR-B monotherapy provide excellent BRFS in intermediate-risk PC. Longer-term follow-up is necessary to determine the ultimate efficacy of these hypofractionated approaches, but they appear promising relative to standard fractionation outcomes. Abstract : Supplemental Digital Content is available in the text.